Quantitative analysis of leukoaraiosis using diffusion tensor imaging: a retrospective study - Salbini, Siti Nor Fatihah Salbinih (2022)
This research is a retrospective study that focused on quantitative analysis leukoaraiosis with the application of diffusion tensor imaging (DTI). Leukoaraiosis (LA) is a pathological appearance of white matter in the brain which appearing as hyperintensity white matter on T2-weighted image MRI brain scans or CT scans. The images used in this study consisted of DTI images of human brain was obtained using GE 1.5 T MRI system available in Advanced Medical and Dental Institute, Universiti Sains Malaysia from year 2012 to 2013. Four main objectives outlined in the study have achieved. Brain images of 43 subjects with leukoaraiosis retrieved from USM PACS system. Four types of analysis have been performed in this study. First is the demographic analysis to have an overview on the gender, age, number of lesion spots and lesion size. This demographic analysis showed that there were more female subject participated in this study. The most subject were aged from 50 to 59 years old. Then, comparison of DTI values of genu and splenium in corpus callosum between subjects with and without leukoaraiosis was performed. It was found that AD (p = 0.70 ; p = 0.46), RD (p = 0.71 ; p = 0.33), MD ( p = 0.67 ; p = 0.34) and FA values (p = 0.67 ; p = 0.34) of genu and splenium in subjects with leukoaraiosis does not differ significantly from those without leukoaraiosis in the two areas. Next, investigation on the intra- and inter-subject variability has been performed for those who have 10 lesion spots and above (≥10), (n = 8). Six subjects showed insignificant differences of FA and LNR while two subjects showed significant differences of FA and LNR within subjects. There are variation of FA and LNR values across lesion sizes within subjects where the smallest lesion got lower FA and higher LNR values and the biggest lesion got slightly difference between FA and LNR values. For inter-subject variability, the subjects have significant difference of FA and LNR. The FA and LNR values varies across the number of lesions. Finally, comparison of FA and LNR values was performed to assess severity of leukoaraiosis tissue changes between subjects who has few big lesions and those with many lesions but having similar total lesion volume. It was found that subjects with many small lesion spots exhibit lower FA values and higher LNR values compared to those with few big lesion spots which indicates that those with many small lesion spots have more severe tissue damage than those few big lesion spots.